Self-Compacting Concrete with incorporation of Recycled Concrete Aggregates - Kamaruddin, Sufian (International Journal of Integrated Engineering, 2019)
At the present the natural resources of aggregates are decreasing day by day due to usage of aggregates in construction industry rises. To overcome this problem, Self-Compacting Concrete (SCC) consisting recycled concrete aggregate (RCA) has the potential to save the natural resources of aggregate and reduces the solid waste generation. In this research, natural aggregates were replaced using RCA at different percentages ranging from 0% to 100% with an increment of 25%. The mechanical properties like filling ability, passing ability, segregation resistance, compressive and tensile strength of M30 grade SCC were examined at 7 and 28 days water curing regimes. Based upon the results it was observed that the slump flow decreased when RCA was incorporated. Furthermore, similar trend was observed in the compressive and tensile strength of SCC containing RCA where 4% to 6% loss in strength was observed compared to control sample.